Astrocytes: GABAceptive and GABAergic Cells in the Brain - Liu, Jianhui; Feng, Xuanran; Wang, Yi; Xia, Xiaohuan; Zheng, Jialin C. (Frontiers in Cellular Neuroscience, 2022)
Astrocytes, the most numerous glial cells in the brain, play an important role in preserving normal neural functions and mediating the pathogenesis of neurological disorders. Recent studies have shown that astrocytes are GABAceptive and GABAergic astrocytes express GABAA receptors, GABAB receptors, and GABA transporter proteins to capture and internalize GABA. GABAceptive astrocytes thus influence both inhibitory and excitatory neurotransmission by controlling the levels of extracellular GABA. Furthermore, astrocytes synthesize and release GABA to directly regulate brain functions. In this review, we highlight recent research progresses that support astrocytes as GABAceptive and GABAergic cells. We also summarize the roles of GABAceptive and GABAergic astrocytes that serve as an inhibitory node in the intercellular communication in the brain. Besides, we discuss future directions for further expanding our knowledge on the GABAceptive and GABAergic astrocyte signaling.